ФЛОТАЦИОННОЕ ОБОГАЩЕНИЯ РУД НИЖНИХ ГОРИЗОНТОВ ДЖИЖИКРУТСКОГО МЕСТОРОЖДЕНИЯ И РЕЗУЛЬТАТЫ ИХ АНАЛИЗА - Холов, Холмахмад; Курбон, Санавбари; Джуракулов, Шерзод (Theoretical and experimental chemistry and modern problems of chemical technology, 2023)
The study of the influence of various modifiers and other factors on the flotation of the studied ores from the lower horizons of the Dzhizhikrut deposit revealed the feasibility of using a simple scheme for this ore to obtain antimony concentrate. Based on the research carried out, a technological scheme for flotation of ore from this deposit is proposed. The article also examines the atomic-molecular structure of the flotation products of gold-antimony-mercury ores based on X-ray scattering. These products were analyzed on a high-tech general purpose X-ray diffractometer DRON-3.